AVALIAÇÃO DO DESEMPENHO E DAS EMISSÕES GASOSAS DECORRENTES DO USO DE BIODIESEL DE SOJA E DE SEBO BOVINO EM DIFERENTES MISTURAS COM O DIESEL EM UM MOTOR GERADOR - Gauer, Mayara Ananda (2012)
Most of the energy consumed on the planet comes from fossil fuels, which are a source of non-renewable energy, and with limited forecasting future depletion. In this scenario, the development and demand for alternative energy sources become relevant. This study aimed to evaluate the differences of pollutant emissions from soybean and tallow beef biodiesel and their blend with diesel (B0, B5, B20, B50 and B100). To perform the tests we used Diesel Interior Type A, soybean biodiesel and beef tallow biodiesel in a diesel engine with direct injection and power of 7.36 kW (10 hp) coupled to a generator of 5.5 kW. To evaluate the performance of the engine was determined the mass consumption, brake specific fuel consumption and energetic consumption to the various fuel blends as well. The efficiency of conversion of each fuel in energy was also determined. For the evaluation of particulate matter we used a pulp fiber filter. The exhaust emissions of inorganic gases have been performed by a Bacharach portable gas analyzer. The BTEX were sampled according to the method TO-17 of USEPA, which prescribes the use of adsorbent resin for the capture of organic gases. The method of BTEX analysis included the use of gas chromatograph (GC) coupled to a thermal desorption unit (ATD) and a flame ionization detector (FID). The results indicated that there was no statistical difference between the specific consumption of diesel and biodiesel used, the energy consumption of diesel was slightly higher than that of biodiesel used and the efficiency of conversion of fuel to energy increased when provided greater load as if the engine and biodiesel added to diesel. Regarding the emissions of particulate material, it was found that the concentration by weight retained on filter was about 50% lower with the use of biodiesel, for both loading conditions applied (0.5 kW and 1.5 kW). CO emissions decrease with the use of soybean biodiesel (BS 100) about 48%, 55% and 46% under loads of 0.5 kW, 1.0 kW and 1.5 kW, respectively. In relation to the use of biodiesel animal fat (BG 100) results led to a reduction of 65% under the load of 0.5 kW and 66% for loads of 1.0 kW and 1.5 kW. SO2 reduction percentages were 72%, 73% and 80% for B100, in loads of 0.5 kW, 1.0 kW and 1.5 kW respectively. Already, with the BG 100 was achieved by reductions of 80% (for the 0.5 kW load) and 76% (for loads of 1.0 and 1.5 kW) compared to diesel. NOx emissions increased in higher load conditions. The highest concentrations were observed for BG 100, in loads of 0.5 kW and 1.0 kW (46% and 57% higher, respectively, compared to petrodiesel). The emissions reported significant reduction in BTEX, in relation to diesel, when the use of pure biodiesel. Such reductions were approximately 80% (0.5 kW), 68% (at 1.0 kW) and 37% (1.5 kW) using the BS 100. For the BG 100, the reductions of total BTEX were 95%, 85% and 73% under loads of 0.5 kW, 1.0 kW and 1.5 kW, respectively. It was concluded that the use of biodiesel in motor generator showed environmental advantages, since promoted reduction of a large quantity of polluting gases released to the atmosphere and did not affect significantly the performance (specific consumption and efficiency) of the engine. It is suggested for future work, which are also held engineering evaluations engine generator to determine which mechanical factors induce an increase / decrease in emissions when the use of biodiesel as a fuel.